Factors favouring or hindering the market entry of Finnish environmental firms in India - Ruggiero, Salvatore (2009)
Environmental technology is one of the promising sectors of the Finnish economy. Environmental firms from Finland are looking with growing interest at the possibilities for entering emerging markets, such as China or India. This Master’s thesis aimed at providing some understanding about how Finnish environmental technology could be exported to India by identifying factors that favoured or hindered the entry of the first generation of Finnish environmental companies in the country. In particular, the study tried to uncover the main success factors for doing business with green technology in the Indian market and the importance of the Finnish origin in this respect. For this purpose, a qualitative research, including seven semi-structured interviews, was conducted. The examination of the data collected at five Finnish environmental firms and the Italian Trade Commission in India, showed that previous indirect presence in the Indian market, reputation and technical competence of the Finnish enterprises were favouring factors for market entry. By contrast, lack of price competitiveness, legislation, bureaucracy and corruption appeared among the main hindrances. Based on these results, it was concluded that to enter the Indian market successfully a solid Indian platform was required. In addition, to avoid lack of price competitiveness the adoption of an alternative strategy from the part of the companies willing to enter the Indian market was perceived as necessary. A successful strategy could be based on either cost minimization or differentiation of the ”made in Finland” brand.